PENGARUH KONSENTRASI GARAM DAN LAMA WAKTU PERENDAMAN TERHADAP CITA RASA IKAN TERBANG (Hirundichthys oxycephalus) - Nanda Usmany; S Liline (BIOPENDIX, 2018)
Background: Flying fish (Hirundichthys oxycephalus) is one type of fish that has a high economic value in Maluku waters. Flying fish (Hirundichthys oxycephalus) are usually consumed in the form of salted fish. However, not all salting techniques in salted fish produce good products and guaranteed quality. This study aims to determine the effect of salt concentration and immersion time on the taste of dried salted (Hirundichthys oxycephalus) flying fish. Methods: This study was analyzed descriptively to assess organoleptics based on panelists using certain scores for the categories of appearance, aroma and taste. The research was conducted from September 5 to 19 2018. Results: The study showed that the best products for processing dried salted fish were 40% salt concentration and 3-hour immersion time which obtained an organoleptic value of 5.91. Conclusion: salt concentration and immersion time did not give a significant effect on the parameters of appearance, aroma, but affect the taste of dried salted flying fish